2014
DOI: 10.7287/peerj.preprints.189
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Upward nitrate transport by phytoplankton in oceanic waters: balancing nutrient budgets in oligotrophic seas

Abstract: In oceanic gyres, primary producers are numerically dominated by small (1-5 µm diameter) pro-and eukaryotic cells that primarily utilize recycled nutrients produced by rapid grazing turnover in a highly efficient microbial loop. Continuous losses of nitrogen to depth by sinking, either as single cells, aggregates or fecal pellets, are balanced by both nitrate inputs at the base of the euphotic zone and nitrogen-fixation. This input of N (new nitrogen) to balance export losses (the biological pump) is a fundame… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…Currently, only a few genera of diatoms are known to form symbiotic relationships with diazotrophs. Further, Rhizosolenia is known to exist without Richelia [10] suggesting this partnership is facultative. Although the transfer of N from symbionts to diatom hosts has been demonstrated [6,11], there are no long-term cultures of this symbiosis to study and our current understanding of this association in situ is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, only a few genera of diatoms are known to form symbiotic relationships with diazotrophs. Further, Rhizosolenia is known to exist without Richelia [10] suggesting this partnership is facultative. Although the transfer of N from symbionts to diatom hosts has been demonstrated [6,11], there are no long-term cultures of this symbiosis to study and our current understanding of this association in situ is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Flagellate motility and cyanobacteria buoyancy control has been recognized for decades as a strategy to exploit spatially disjunct light and nutrient fields (Cullen, 1985;Eppley et al, 1968, Ganf andOliver, 1982;Hasle, 1950;Steemann Nielsen, 1939) and was first suggested for non-flagellated marine species in Pyrocystis (Ballek and Swift, 1986;Rivkin et al, 1984). Fraga et al (1992Fraga et al ( , 1999 (Villareal et al, 1993, Villareal et al, 2014, internal millimolar nitrate pools that can only be acquired by direct uptake at µM concentrations (Villareal and Lipschultz, 1995;Villareal et al, 1996;Woods and Villareal, 2008), buoyancy reversals linked to nutrient status (Richardson et al, 1996), nitrate reductase activity (Joseph et al, 1997) induced only when nitrate is the primary N source, ascent/descent rates of m hr -1 (Villareal et al, 2014;Moore and Villareal 1996), observation of Rhizosolenia mats from the surface to 305 m (Pilskaln et al, 2005), and compositional difference in floating and sinking mats that mirror physiological changes associated with nutrient depletion and carbohydrate ballasting (Villareal et al, 1996). The m hr -1 ascent/descent rates permit the necessary 50-100 m vertical excursions and when coupled with the large vacuole of these giant phytoplankton, allow the necessary storage (mM concentrations in vacuoles that are 90+% of total cell volume) for a multiple day migration and division cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Giant phytoplankton are found throughout the warmer oceans of the world and the required characteristics of buoyancy reversals, high internal nitrate pools and rapid ascent have been found in multiple taxa from the Atlantic and Pacific Oceans (Villareal et al, 2014). Unlike the more widely known zooplankton vertical migration, open ocean phytoplankton migration is a multi-day cycle (Richardson et al, 1998;Villareal et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…However, active water transport may also be a mechanism for planktonic cells to adjust their buoyancy. In an environment where light and nutrients are often spatially separated, vertical adjustment relative to the water surface may be a competitive strategy to gain access to nutrients at depth (Doblin et al, 2006;Villareal et al, 2014).…”
Section: Active Water Transport In Effectively Wall-less Freshwater Cmentioning
confidence: 99%